All quiet on the Western Front?: the creation and perception of self-made instruments in the trenches of the First World War - Schmidt, Johanna de (The journal of musicological research, 2014)
During the First World War musical instruments were not only present on the Western Front; they were also manufactured by soldiers. They enabled soldiers to play music during their stay in the trenches and were critical components of the soldiers’ daily lives. Musical instruments, both professional and self-made, were highly valued by their possessors and sometimes even seen as a comrade, a fellow sufferer in the pernicious environment of the Western Front.